Psychological Impacts of Students on Online Learning During the Pandemic COVID-19 - Irawan, Andi Wahyu; Dwisona, Dwisona; Lestari, Mardi (Universitas Islam Negeri Raden Intan Lampung, 2020)
The Indonesian government formally enforces rules of study, worship, and work from home from March 16, 2020. Minimizing and limiting meetings involving physical contact is an effort to reduce the spread of the COVID-19 virus. These conditions have implications for the effectiveness of the learning process in higher education. The purpose of this study was to identify the impact of student psychology on online learning during the COVID-19 pandemic. The research method uses a qualitative research type of phenomenology. The research subjects were 30 students of Mulawarman University who were interviewed via telephone. The research findings show that (1) students have started to get bored with online learning after the first two weeks of learning from home, (2) considerable anxiety on research subjects whose parents have low income, because they have to buy quotas to be able to participate in online learning, ( 3) mood or mood changes occur due to too many assignments and are considered ineffective by students. Suggestions and recommendations from this research are the need for severe efforts in assisting the psychological well-being of students through the involvement of counselors and psychologists.